Genome-guided insight into the methylotrophy of Paracoccus aminophilus JCM 7686 - Dziewit, Lukasz; Czarnecki, Jakub; Prochwicz, Emilia; Wibberg, Daniel; Schlüter, Andreas; Pühler, Alfred; Bartosik, Dariusz (Frontiers in Microbiology, 2015)
Paracoccus aminophilus JCM 7686 (Alphaproteobacteria) is a facultative, heterotrophic methylotroph capable of utilizing a wide range of C1 compounds as sole carbon and energy sources. Analysis of the JCM 7686 genome revealed the presence of genes involved in the oxidation of methanol, methylamine, dimethylamine, trimethylamine, N,N-dimethylformamide and formamide, as well as the serine cycle, which appears to be the only C1 assimilatory pathway in this strain. Many of these genes are located in different extrachromosomal replicons and are not present in the genomes of most members of the genus Paracoccus, which strongly suggests that they have been horizontally acquired. When compared with Paracoccus denitrificans Pd1222 (type strain of the genus Paracoccus), P. aminophilus JCM 7686 has many additional methylotrophic capabilities (oxidation of dimethylamine, trimethylamine, N,N-dimethylformamide, the serine cycle), which are determined by the presence of three separate gene clusters. Interestingly, related clusters form compact methylotrophy islands within the genomes of Paracoccus sp. N5 and many marine bacteria of the Roseobacter clade.